2019
DOI: 10.1080/2090598x.2019.1611990
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin glue as a sealant in stentless laparoscopic pyeloplasty: A randomised controlled trial

Abstract: Objective : To evaluate the value of adding fibrin glue, as a sealant material, to the anastomotic line during stentless laparoscopic pyeloplasty (LPP). Patients and methods : In all, 92 patients with pelvi-ureteric junction obstruction (PUJO), scheduled for LPP, were randomised into two groups (46 in each group). Group A, underwent transperitoneal stentless LLP sealed with fibrin glue, whilst Group B underwent the same procedure without fibrin glue. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It is also impractical to reduce (resect) the pelvis during pyeloplasty because it does not affect the outcome of the operation [20]. One author presents two similar works demonstrating the effectiveness of fibrin glue during pyeloplasty according to the tubeless protocol, which reduces urine leakage and improves treatment outcomes [21]. We consider it expedient to reduce surgical trauma further by using mini laparoscopic techniques, which is confirmed by some early works [22].…”
Section: Discussionmentioning
confidence: 85%
“…It is also impractical to reduce (resect) the pelvis during pyeloplasty because it does not affect the outcome of the operation [20]. One author presents two similar works demonstrating the effectiveness of fibrin glue during pyeloplasty according to the tubeless protocol, which reduces urine leakage and improves treatment outcomes [21]. We consider it expedient to reduce surgical trauma further by using mini laparoscopic techniques, which is confirmed by some early works [22].…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, our study showed that the procedure is repeatable and that results are reliable over time as showed by our relative long follow-up of approximately 12 months. The use of FG as a hemostatic agent have been previously studied in urological surgery and the use of the Vivostat ® system have been proven to be effective and safety when applied to urological surgery, in particular to prevent bleeding in renal surgery and lymphatic leakage in lymphadenectomy (18)(19)(20)(21). However, only few studies investigated its use for the treatment of HC.…”
Section: Discussionmentioning
confidence: 99%